2010
DOI: 10.5539/jas.v2n4p211
|View full text |Cite
|
Sign up to set email alerts
|

Child Street - Trading Activities and Its Effect on the Educational Attainment of Its Victims in Epe Local Government Area of Lagos State

Abstract: This study examined child street trading activities and its effect on the educational attainment of its victims in Epe local government area of Lagos State. One hundred and twenty (120) respondents were selected from 6 communities using purposive sampling techniques, administered by means of interview guide. Children interviewed were between 10 and 18 years of age. Descriptive statistics and inferential statistics were used in data analysis. The study revealed that most (60.8%) of the children who engaged in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Also, the issue of children hawkers has been used to argue that street trading has negative impact on even the under age. Ashimolowo et al [15] studied the effect of child street trading activities and found that street trading has negative effects on children. Further, it was noted that there is a high tendency for the girl child to forgo her education and thereby lose all the benefits of education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the issue of children hawkers has been used to argue that street trading has negative impact on even the under age. Ashimolowo et al [15] studied the effect of child street trading activities and found that street trading has negative effects on children. Further, it was noted that there is a high tendency for the girl child to forgo her education and thereby lose all the benefits of education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Epe is a major source of supply of food to Lagos State (Mohammed et al, 2015). The rural communities in Epe include: Naforija Odomola, Epe, Ilara, Otta-Ikosi, Ejinrin, Eredo, Odoragunsen, Mojoda, Ibowon, Itoikin, Ketu, Odo-Ayandelu, Orugbo, Igbonla, Ita oko, Yegunda, Molajoyo Oke egun, Erinmope, Iganke, Araga, and Aferan among others (Ashimolowo et al, 2010). It is located about 90 kilometres to the Northeast of Lagos metropolis (Babalola & Aina, 2004).…”
Section: Area Of Studymentioning
confidence: 99%
“…Peddling through the streets in developing countries is another area of interest the researchers will love to explore (Olutunde, 2013;Ugochukwu et al, 2012) due to the socio-economic and negative health effects that can results from this by those who involved in it. (Amoo et al, 2012;Esin et al, 2005;Ashimolowo et al, 2010). Developing countries are faced with exponential growth giving rise to rural-urban drift in search of a better means of livelihood (Hoyamo and Keenan, 2007).…”
Section: Introductionmentioning
confidence: 99%